Large-area versus Small-area Application of Mitomycin C during Trabeculectomy. Issue 5 (September 2013) - Matlach, Juliane; Panidou, Ermioni; Grehn, Franz; Klink, Thomas
Purpose: To compare 2 different application methods of mitomycin C (MMC) in patients undergoing trabeculectomy . Methods: This retrospective trial compared outcomes of 191 eyes that underwent trabeculectomy with small-area (96 eyes; 50.3%) and large-area (95 eyes; 49.7%) MMC application. Main outcome measures were changes in intraocular pressure (IOP), required glaucoma medications, the frequency of complications, and postsurgical interventions . Results: Within both treatment groups, a highly significant IOP reduction was seen during follow-up (p < 0.0001). Statistical analyses revealed a significant difference in IOP between both groups. Patients treated with a larger size of surface area had a higher IOP reduction within the first postoperative year. Choroidal detachment, shallow anterior chamber, and bleb leak were seen more often in the large-area group with more aggressive MMC use. In contrast, complications associated with bleb failure such as bleb scarring were higher in the small-area group. Success rate was higher in the large-area MMC application group after 12 months . Conclusions: Large-area treatment seems to be a more efficient application method of MMC during trabeculectomy .